The Problem of Thinking and Language: Concept - Israyelyan, Stela (Armenian Folia Anglistika, 2009)
The article attempts to discuss the nature of the concept in the context of the inter-relationship between thinking and language. Thinking is a process which takes place in the nerve cells of the brain. Language is a means to convey thoughts. Proceeding from the fact that language cannot exist without culture, we come to the belief that concept holds an intermediate position among language, thought and culture.